THE TRIPARTITE RAMSEY NUMBERS r\(_t\)(C\(_4\); 2) AND r\(_t\)(C\(_4\); 3) - Buada, S.; Samana, D.; Longani, V. (Italian Journal of Pure and Applied Mathematics, 2014)
The k-colored tripartite Ramsey numbers rt(G; k) is the smallest positive integer n such that any k-coloring of lines of a complete tripartite graph Kn,n,n there always exists a monochromatic subgraph isomorphic to G. When G is C4 it is known, but unpublished in a journal, that rt(C4; 2) = 3. In this paper we simplify the proof of rt(C4; 2) = 3 and show the new result that rt(C4; 3) = 7.